“Evaluación de las propiedades físico-químicas del aceite pirolítico a partir de biomasas sometidos al proceso de pirólisis convencional”. - Espín Espín, Henry Daniel (2020)
The pyrolytic acid production process is an alternative for the use of biomass that in most cases is considered as waste, without considering that they can be used to obtain said product that you have multiple uses. However, depending on the biomass used, its properties may vary. Therefore, the present investigation aimed to evaluate the physicochemical properties of pyrolytic oil from biomass subjected to the conventional pyrolysis process. The essay was carried out at the “La María” Campus of the State Technical University of Quevedo. Three treatments were evaluated, consisting of the biomass under study: rice husk (Oryza sativa L.), guadua bamboo (Guadua angustifolia) and Neem (Azadirachta indica). The process of producing pyrolytic acid was characterized by a handmade reactor that allowed obtaining said acid by simple condensation and analyzes of its nutritional composition were performed. As main results, it was possible to show that the characterization of the process of obtaining pyrolytic acid from the three types of biomass showed that rice husk, being a dry biomass and of uniform distribution in the reactor, allows burning to begin in approximately 10 minutes while that the Neem and guadua bamboo take 15 and 17 minutes to start this process, respectively. The acids obtained from different biomass showed similar characteristics of color (very dark brown), taste (spicy acid) and smell (smoke), however, they differ in their nutritional composition, being that obtained from Neem the one with the highest N content (2.70 %), K (0.07%), S (0.06%) and Zn (5.00 ppm), with a pH of 5.82 (closer to neutral), while using rice pad, a higher P content (0.03%) was obtained , Fe (190.00 ppm) and Cu (5.00 ppm), the content of B (21 ppm) being higher in that of guadua bamboo. The same content of Mg (0.02%) and Mn (1.00 ppm) was obtained in all three biomass, while the same content of Ca (0.31%) was obtained with the biomass of rice and guadua bamboo. Keywords: pyrolytic acid, agroecology, plant biomass.